Use of an Anastomotic Coupling Device for the Creation of Spliced Autogenous Grafts in Lower Extremity Revascularization. (April 2015) - Golas, Alyssa R.; Jacoby, Adam; Karwowski, John K.; Spector, Jason A.
Introduction: Despite a recent rise in popularity of endovascular techniques, open bypass surgery is still required for treating many lower extremity vascular lesions. Greater saphenous vein (GSV) of adequate length and caliber for successful infrainguinal lower extremity bypass is unavailable in 15% to 45% of patients. To overcome limitations imposed by absent vein due to prior use, short vessel length, or sclerotic segments, both alternate (ie, basilic and cephalic) and GSV conduits may be "spliced" together in series via venovenostomy. Although vascular surgeons typically perform a hand-sewn venovenostomy, device-based venous coupling has been performed by plastic surgeons for many years. We therefore sought to review our experience with venous coupling for segmental lower extremity bypass graft assembly. Methods: A retrospective review was performed in all patients who underwent lower extremity revascularization using autogenous vein grafts spliced together with the Synovis (Birmingham, Alabama) anastomotic coupler at a single institution over a 5-year period. Results: The anastomotic coupler device was used on 5 patients for 7 venovenostomies. The mean age of patients was 66 years, and the mean follow-up period was 751 days. Two patients were lost to follow-up, while 2 other patients died of causes unrelated to their lower extremity bypass. The average time to perform venovenostomy was 3 minutes. Three patients developed stenosis of their composite graft at a site other than the venovenostomy, who were successfully treated with either angioplasty or bypass revision. One-year primary and primary-assisted patency rates were 50% and 75%, respectively. Conclusions: Given the known benefits of the anastomotic coupling device when used for venous anastomoses in microsurgical reconstruction, transition of this device to the vascular surgery realm represents a logical progression. Although small, our series demonstrates that the anastomotic coupler can successfully be used for the formation of spliced autogenous grafts for lower extremity revascularization in the absence of adequate GSV.